Design and implementation of a knowledge base for the office of the Vice Mayor Of Marikina City’s COVID-19 effort - Santos, Patcheska Dewi R.; Dorado, Dan Anthony D.; Perez, Paul Jason V. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2021)
Knowledge bases are used for different purposes, depending on the information needs and system that will best suit an institution. For this project, the system will solely focus the COVID-19 pandemic efforts of the OVM that will be deemed needed for a knowledge base. Interviews with the stakeholders were conducted in order to understand the records processes as well as to gather data to figure out how the OVM knowledge base will be designed and developed. Knowing the stakeholders as well as their participation in the project is necessary as this also indicates the requirements that the project manager must meet and strategies to be done.

In conducting the project, the ADDIE Waterfall Model served as a guide. The project followed the linear hierarchical structure of the ADDIE Waterfall Mode. The project manager started with the Design and Development phase and so on. During the Design and Development phase, Nation, was configured to meet the requirements of the stakeholders. Before the project closeout, an online survey was conducted to let the stakeholders who participated in the project implementation, evaluate the knowledge base application as and give their recommendations and suggestions regarding the system.

This project revealed the importance of a knowledge base in an institution specially when dealing with data. Having a KB does not only entail productivity and efficiently within the institution but also enables the team to provide better services to its customers. In addition, this can pave way for future endeavors concerning the OVM and other public and private institutions. Furthermore, this can serve as a framework for similar knowledge base system implementations in the future.
Special Problem
Keywords: Marikina (Philippines). -- Office of the Vice Mayor; Knowledge management; COVID-19 Pandemic, 2020-2023 -- Philippines; Local government -- Marikina (Philippines).